1992
DOI: 10.1111/j.1365-2761.1992.tb00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of monoclonal antibodies for the rapid identification of epizootic Vibrio species

Abstract: . A library of monoclonal antibodies has been developed for use in rapid diagnosis of Vibrio infecftions. It covers the Vibrio Species that are regarded as the major fish and shellfish pathogens, many of which are also human pathogens. Blind tests confirm the accurary of the monoclonals as a diagnostic test. Conjugation of enzyme lable onto the monoclonals is providing rapid identification of Vibrio species by use of direct, rather than indirect, immunological testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
1
4
0
1
Order By: Relevance
“…Serological assays indicated that the V. ordalii isolates were highly homogeneous because whole cells and 0 antigens produced strong slide agglutination and ELISA with antisera raised against isolate 1 and CECT-582. These two assays showed that the ten V. ordalii strains were antigenically homogeneous and no serotypes were detected, as described by other researchers (Toranzo et al, 1987;Hanna et al, 1991;Chen et al, 1992;Grisez and Ollevier, 1995;Austin et al, 1997).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Serological assays indicated that the V. ordalii isolates were highly homogeneous because whole cells and 0 antigens produced strong slide agglutination and ELISA with antisera raised against isolate 1 and CECT-582. These two assays showed that the ten V. ordalii strains were antigenically homogeneous and no serotypes were detected, as described by other researchers (Toranzo et al, 1987;Hanna et al, 1991;Chen et al, 1992;Grisez and Ollevier, 1995;Austin et al, 1997).…”
Section: Discussionsupporting
confidence: 80%
“…Enzyme-linked immunosorbent assay (ELISA). An indirect ELISA was used to detect the antibody in the antirabbit serum samples against Vibrio species, as described by Arkoosh and Kaattari (1990) and Hanna et al (1991). Each bacterial suspension was added to each well of a 96-well microtiter plate.…”
Section: Methodsmentioning
confidence: 99%
“…Vibriosis is caused by species of Vibrio , namely by Vibrio anguillarum [ 7 9 ]. Others species of Vibrio , such as V. alginolitycus , V. anguillarum , V. carchariae , V. salmonicida , V. damsela , V. ordalii , V. parahemolyticus and V. vulnificus , causes also important infections in several species of fish [ 10 , 11 ]. Photobacteriosis is caused by Photobacterium damselae subsp.…”
Section: Introductionmentioning
confidence: 99%
“…V. parahaemolyticus, indeed, is a human bacterial pathogen widely occurring in marine environments, frequently isolated from a variety of seafood, including bivalves, crustaceans, and fish [67]. Vibriosis is currently responsible for most disease outbreaks in aquaculture [31][32][33][34]68].…”
Section: Discussionmentioning
confidence: 99%
“…In highly anthropized marine environments, such as intensive or confined mariculture systems, the excessive release of excreta from farmed species and organic matter from uneaten feed create favorable conditions for pathogenic bacteria growth, especially Vibrio, responsible for diseases and high mortality in target species, with consequent economic losses [31][32][33][34][35][36][37]. To overcome this problem, the use of antibiotics has spread despite the increase in production costs and the negative consequences on farmed species and the surrounding environment.…”
Section: Introductionmentioning
confidence: 99%